OSB sandwich panel with undulated core of balsa wood waste - B. Martins, Romulo Henrique; A. Barbirato, Guilherme Henrique; C. Filho, Luiz Eduardo; Fiorelli, Juliano (Maderas. Ciencia y Tecnología, 2023)
The production of wood-based materials is currently being expanded by the furniture industry and civil construction sector. In order to find new alternatives for the panel market, new configuration possibilities (geometry) of panels and the use of renewable raw materials must be explored. In this scope, the objective of this research was to evaluate OSB sandwich panels with an undulated core and flat faces (OSBUC panels) made of Balsa wood waste strands (Ochroma pyramidale) bonded with two-component castor oil polyurethane resin for use in civil construction. Two types of panels were produced with 13 % resin and varying the density of the core (OSBUC-T1 - faces 550 kg/m³ and core 400 kg/m³) and (OSBUC-T2 - faces 550 kg/m³ and core 500 kg/m³). The water absorption and thickness swelling of the face panels were determined based on the Brazilian standard NBR 14810 and the bending test properties of the OSBUC panels determined by the recommendations of the ASTM C393 standard. The results obtained were compared with the specifications of the PS-2-10 –“Performance Standard for Wood-Based Structural-Use Panels” that provides bending stiffness (EI) values and maximum bending moment (FbS) requirements for OSB panels according to different classes of use. The sandwich panels had maximum values of EI 6,48 x 106 N·mm²/mm and FbS 3065 N·mm/mm. The OSBUC-T1 treatment proved to be the most efficient, as it has mechanical properties that meet the normative recommendations for structural use and as flooring, with lower material consumption (lower density).